Designing a novel tomato ideotype for future cultivation in space manned missions - Pagliarello, Riccardo; Bennici, Elisabetta; Cemmi, Alessia; Di Sarcina, Ilaria; Spelt, Cornelis; Nardi, Luca; Del Fiore, Antonella; De Rossi, Patrizia; Paolini, Francesca; Koes, Ronald; Quattrocchio, Francesca; Benvenuto, Eugenio; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Methods for production of fresh, health food are needed in view of long-term, deep-space manned missions. To this end, crops tailored for better performance under non-terrestrial conditions may be obtained by the exploitation of biochemical patterns related to specialized metabolites known to confer protection against environmental challenges and to be beneficial to human health. In this work, for the first time, MicroTom plants have been engineered specifically for agrospace applications to express PhAN4, a MYB-like transcription factor able to regulate the biosynthesis of anthocyanins that influence tomato genes possibly involved in agrospace-relevant functions. PhAN4 engineering underpinned the genetic background of the dwarf tomato MicroTom while maintaining yield and photosynthetic capacity. PhAN4 expression resulted in the accumulation of anthocyanins and polyphenols, a differential carotenoid profile, increased antioxidant scavenging capacities of fruits compared to the original genotype. Improved ability to counteract ROS generation and to preserve plant protein folding after ex-vivo gamma irradiation was observed. These results highlights that the manipulation of specific metabolic pathways is a promising approach to design novel candidate varieties for agrospace applications.